2015
DOI: 10.3390/chemosensors3020178
|View full text |Cite
|
Sign up to set email alerts
|

Development of Solid-State Electrochemiluminescence (ECL) Sensor Based on Ru(bpy)32+-Encapsulated Silica Nanoparticles for the Detection of Biogenic Polyamines

Abstract: Abstract:A solid state electrochemiluminescence (ECL) sensor based on Ru(bpy)3 2+ -encapsulated silica nanoparticles (RuNP) covalently immobilised on a screen printed carbon electrode has been developed and characterised. RuNPs were synthesised using water-in-oil microemulsion method, amino groups were introduced on their surface, and they were characterised by transmission electron microscopy. Aminated RuNPs were covalently immobilised on activate screen-printed carbon electrodes to form a solid state ECL bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Regular physiological functions demand an optimum balance of ubiquitous biogenic amines such as spermidine and spermine in biological systems. Unregulated or excess concentrations of these molecules have been reported to be detrimental, causing serious health issues such as apoptosis, respiratory disorders, cardiac palpitation, brain hemorrhage, heart palpitation, chronic gastritis, allergies, and cancer. Although there are several reports presenting sensitive and selective determination of these bioamines, ,,, they are time-consuming, cost-intensive procedures requiring laborious sample preparation, with expertise in handling. In this context, optical sensing platforms such as SPCE present easy to perform, fast, and reliable methodology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular physiological functions demand an optimum balance of ubiquitous biogenic amines such as spermidine and spermine in biological systems. Unregulated or excess concentrations of these molecules have been reported to be detrimental, causing serious health issues such as apoptosis, respiratory disorders, cardiac palpitation, brain hemorrhage, heart palpitation, chronic gastritis, allergies, and cancer. Although there are several reports presenting sensitive and selective determination of these bioamines, ,,, they are time-consuming, cost-intensive procedures requiring laborious sample preparation, with expertise in handling. In this context, optical sensing platforms such as SPCE present easy to perform, fast, and reliable methodology.…”
Section: Resultsmentioning
confidence: 99%
“…There are several reports that emphasize monitoring spermidine levels in urine, saliva, and biological fluids for early diagnosis of malignancy. Therefore, it is worth mentioning that although biogenic polyamines remain an essential component for normal physiological functioning, their altered concentrations can have several implications and hence require constant monitoring . In light of these observations, different methods including high-performance liquid chromatography (HPLC), gas chromatography–mass spectrometry (GCMS), thin-layer chromatography, radioimmunoassay, different fluorescent bioprobes using dye-embedded micelles, sol–gel films and conjugated polymers, capillary electrophoresis, and electroanalytical methods have been employed to monitor spermidine concentrations at significantly low limits. ,, However, the limit of detection that has been achieved so far is at nanomolar concentrations. ,, In this context, there is a driving need for rapid, convenient, reproducible, highly sensitive, and selective determination of spermidine in various biological systems including terrestrial and aquatic life forms, molecular diagnostics, and food industries. Unlike the cost intensive spectrophotometer detection platforms that are commonly used for this purpose, in this study we demonstrate a label-free smartphone-based SPCE detection technique that is portable and economically viable for resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of mixed oxides and organic groups can be of high importance in this field to avoid leaching of these dyes during usage [13]. It is also possible to manufacture different devices' configuration such as nanosensors for pH measurement [13], optical fibers for volatile organic compounds' detection [14], electrochemical [15], electrochemiluminescence [16] and biosensors [17]. Furthermore, silica is commonly used to protect or give special features to surfaces.…”
Section: Introduction On Silica-based Materialsmentioning
confidence: 99%
“…[ 48 ] However, the decreased ECL intensity in higher pH buffers may have resulted from the insolubility of TPA [ 49 ] and low availability of Ru(bpy) 3 3+ . [ 50,51 ] This reduced availability would then induce poor ECL efficiency due to the competitive reaction of the OH radical, which consumes large amounts of Ru(bpy) 3 3+ at a high pH. Since the useful pH range for the sodium tetraborate (STB) buffer is 8.5–10.5, we confirmed that the ECL intensity at pH 8.5 was higher than that at pH 9.5 and ultimately selected a pH of 8.5 as the optimal condition (Figure S10a, Supporting Information).…”
Section: Resultsmentioning
confidence: 65%